Green Marketing and Sustainable Product Impacts on Customer Purchasing Intention: Case Study of Fast Moving Consumer Goods Product - Etty Zuliawati Zed; Sesri Sellinai; Tri Mulyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
.This study investigates the influence of green marketing and sustainable product attributes on customer purchasing intention within the fast-moving consumer goods (FMCG) sector, using brand image and trust as mediating variables. With heightened environmental awareness, consumers increasingly favor eco-friendly brands and products, yet their actual purchasing behavior may be affected by factors such as brand image and skepticism about green claims. The study's findings confirm that green marketing positively impacts brand image, which subsequently enhances purchasing intention, while sustainable product attributes significantly influence customer intentions directly. Utilizing survey data from 300 respondents and analyzing results through Partial Least Squares Structural Equation Modeling (PLS-SEM), the study provides insights for FMCG companies aiming to leverage sustainability as a competitive advantage. The implications suggest that transparent green marketing and authentic sustainable practices are critical in building trust and loyalty among eco-conscious consumers